Future prospects - Diao, Xinshen; Hazell, Peter B. R.; Kolavalli, Shashidhara; Resnick, Danielle (International Food Policy Research Institute, 2019)
This final chapter pulls together the main findings of the book, highlights future challenges and opportunities for Ghana, and provides some guidance on the kinds of strategic changes that might help the country’s efforts towards more sustained structural change. It also concludes with some reflections on what the Ghanaian experience suggests for the rest of Africa.